Scientific and social response to 2006-07 activity at Ubinas volcano, southern Peru - Lautze, Nicole C. (2007)
Póster (21a-P-09) presentado en Cities on Volcanoes 5 conference : Shimabara, Japan, November 19-23, 2007.